Representation of the Role of a Mother in the Mother's Version of Dancow Advertising is Not Perfect but Mother's Love Always is there - Rafi Nafis; Reni Nuraeni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The phenomenon of women as mothers who work and educate children has its own challenges. A mother is required to maintain communication with her child and also be professional at work. The mother can be the head of the family who has responsibility for the family, by managing all household matters including children, and this shows the importance of a mother in the family other than the father. Seeing how women as mothers are represented in a media and considering the progress of a mother's representation in the general world, the researchers are interested in seeing how mass media such as advertisements on YouTube describe the role of a mother. This makes advertising through YouTube more accessible to the wider community and in large numbers. In addition, making advertisements on YouTube will be able to be enjoyed by the public for a longer time because the duration of the video is longer than other social media or television. In this study, the researcher used a qualitative research method with a semiotic theory approach of Roland Barthes. The subject of the research focuses on the representation of the role of a mother in the Dancow version of the Mother Not Perfect But Mother's Love is Always There. Researchers have determined 8 scenes / scenes to identify research problems. The researcher's goal in determining these scenes is to fit the research focus that has been discussed in the previous chapter. The researcher analyzed 8 scenes of Dancow's milk commercial, Mother's version is not perfect but Mother's Love is always there to analyze the representation of a mother's role.